Evaluasi Kelas Unggulan dalam Meningkatkan Kualitas Pendidikan di SD Negeri Sungai Nepal - Fenti Harianti; Bukman Lian; Meilia Rosani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to evaluate the implementation of the Excellence Class program as an effort to improve the quality of education at SD Negeri Sungai Nepal. The Excellence Class is a strategic initiative designed to provide enriched learning experiences, foster students’ potential, and create a competitive academic atmosphere. Using a qualitative descriptive approach, data were collected through in-depth interviews with school leaders, teachers, students, and parents, supported by classroom observations and document analysis. The findings reveal that the Excellence Class has contributed significantly to enhancing students’ academic achievement, critical thinking skills, and motivation to learn. Teachers reported improved classroom management and the ability to implement innovative learning strategies that align with the independent curriculum. Furthermore, parental involvement increased through regular communication and collaborative activities, which strengthened the school–community partnership. Despite these positive outcomes, several challenges remain, including limited learning resources, varying teacher readiness, and the need for continuous professional development to maintain program sustainability. The study concludes that the Excellence Class program serves as an effective model for improving educational quality when supported by strong leadership, adequate resources, and active stakeholder participation. Recommendations include regular program evaluation, targeted teacher training, and increased investment in learning facilities to ensure long-term success and replicability in other schools.